Pengembangan Media Digital Komik (DESMEDIK) pada Pembelajaran Fiqih di MTsN 3 Jombang - Noermawati Putri; Khoirun Nisa'; Dian Kusuma Wardani (Lembaga Yasin AlSys, 2026)
Although digital learning media have been widely developed in Islamic education, research specifically developing and evaluating the effectiveness of digital comic-based media in Fiqh learning, particularly on the topic of sunnah mu’akkad and ghairu mu’akkad prayers at the Madrasah Tsanawiyah level, remains limited. This study aimed to develop and evaluate the feasibility and effectiveness of DESMEDIK (Digital Comic Media) in Fiqh learning at MTsN 3 Jombang. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The research participants consisted of Grade VIII students at MTsN 3 Jombang, with 10 students involved in the limited trial and 30 students in the field trial. Data were collected through observation, interviews, expert validation questionnaires involving a subject-matter expert, a media expert, and a practitioner, as well as pre-test and post-test assessments, and were subsequently analyzed using quantitative and qualitative descriptive methods. The findings showed that DESMEDIK was categorized as feasible to highly feasible, with validation scores of 3.80 from the subject-matter expert, 3.20 from the media expert, and 3.75 from the practitioner. Students’ responses to the media were also highly positive, with percentages of 90% in the limited trial and 91.7% in the field trial. The effectiveness of the media was demonstrated by an increase in the mean learning outcome score from 60 on the pre-test to 85 on the post-test, accompanied by an increase in learning mastery from 50% to 93.3%. These findings affirm that DESMEDIK is a feasible and effective learning medium for improving students’ understanding of Fiqh material. This study contributes to the development of digital learning media in Islamic Religious Education, particularly the use of digital comics as an alternative medium for Fiqh learning, and provides practical implications for teachers and educational institutions in integrating innovative digital media into the learning process. Future research may examine the implementation of DESMEDIK across more diverse educational contexts and Islamic Religious Education materials.